1996
DOI: 10.1111/j.1472-8206.1996.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of galanin and some of its analogues on rat isolated gastric fundus*

Abstract: The study was undertaken to characterize the effects of porcine galanin (pGal) and some of its analogues on rat gastric fundus muscle strips. pGal, galantide (M15) and pGal(1-14)-[Abu8]SCY-I evoked reproducible concentration-dependent contractions in concentrations of 1-300, 3-1,000 and 100-3,000 nM, respectively, with EC50 values of 13, 70 and 187 nM. Hill's coefficient for pGal is 1.03, indicating an interaction of one pGal molecule with one receptor, fulfilling criteria of classical receptor theory. For M15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…To identify the site(s) of abnormalities responsible for impaired muscle contraction to galanin we measured some pharmacodynamic parameters characterizing the interaction of the peptide with its receptor(s). Our results confirm that galanin, according to the principles of the classical receptor theory, contracts gastric fundus strips by a direct interaction with a specific receptor, as Hill's coefficients calculated from the concentration-contraction curves in the strips from control animals were not different from unity [20,33]. On the contrary, Hill's coefficients estimated from the concentration-contraction curves in STZ rats at 4 and 8 weeks were below unity, values indicating either a heterogeneity of binding sites or modifications in agonist-receptor interactions.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…To identify the site(s) of abnormalities responsible for impaired muscle contraction to galanin we measured some pharmacodynamic parameters characterizing the interaction of the peptide with its receptor(s). Our results confirm that galanin, according to the principles of the classical receptor theory, contracts gastric fundus strips by a direct interaction with a specific receptor, as Hill's coefficients calculated from the concentration-contraction curves in the strips from control animals were not different from unity [20,33]. On the contrary, Hill's coefficients estimated from the concentration-contraction curves in STZ rats at 4 and 8 weeks were below unity, values indicating either a heterogeneity of binding sites or modifications in agonist-receptor interactions.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally Lucas and Sardar [26] suggested that a decreased myogenic response of the terminal ileum to exogenous acetylcholine after 30 days of diabetes may result from changes in the myocytes involving a decrease in the number of muscarinic receptors. A similar hypothesis may apply in our experiments, since STZ-induced diabetes seems to suppress galanin receptors in gastric fundus strips, and the significant reductions in E max to galanin and decreases in the slopes of the appropriate concentration-response curves are not accompanied by changes in EC 50 [7,20]. Clearly appropriate radioligandbinding studies are needed to definitely estab-lish which of the mechanisms is ultimately responsible for the above-mentioned alterations.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…M15 blocks the neuronal action of galanin in the central nervous system [6]. In gastrointestinal smooth muscles galantide acts as a full agonist of galanin [7,8].…”
Section: Introductionmentioning
confidence: 99%